Microtus gregalis - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Microtus gregalis (Pallas, 1778). Nova Spec. Quad. Glir. Ord., p. 238. TYPE LOCALITY: U.S. S. R., R.S.F.S. R., Tomsk. Obi., E. of Chulym River. DISTRIBUTION: Palearctic tundra from White Sea, east to Anadyr region (U.S. S. R.); mountains and steppes of N.C. and S. Siberia from S. Urals to upper tributaries of Amur River, and S. to Pamir (U.S. S. R.), Tien Shan (U.S. S.R. and China), and Altai (U.S. S. R. and Mongolia) Mtns., N. Mongolia, N.E. China, and probably North Korea. COMMENT: Subgenus Stenocranius; see Anderson, 1960:200; see comments under miurus. ISIS NUMBER: 5301410008080013001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 492, DOI: 10.5281/zenodo.7353034